Wind tunnel study of ammonia transfer from a manure pit fitted with a dairy cattle slatted floor. Issue 2 (17th January 2016) - De Paepe, Merlijn; Pieters, Jan G.; Mendes, Luciano B.; Van Weyenberg, Stephanie; Merci, Bart; Demeyer, Peter
Abstract : In dairy cattle systems, most of the feces and urine go to the pit. At the manure pit level, mass transfer of NH3 ( ) has many factors, but practical difficulties hamper a controlled field evaluation. In this study, we propose a methodology for the determination of an alternative, more practical, pit transfer coefficient of NH3 ( PTC ), and compare it with determined from other scientific studies. The aims of this research study were: (1) to develop a wind tunnel set-up which mimics air flow patterns between the slats and above a clean section of a slatted floor section, featuring an aqueous NH3 -emitting solution; and (2) to assess how air velocity, turbulence intensity, NH3 concentration ([NH3 ]) and PTC are influenced by inlet airflow ventilation rate ( VR ) forced deflection of the air above the slats into the manure pit through varying the deflection angle ( DA ) of a deflection panel and varying pit headspace height ( HH ). Main conclusions were: (1) the calculated PTC values presented a good fit to the power function of the air speed near the slats ( u ) ( p  < .001) while the average PTC (0.0039 m s −1 ) was comparable to values obtained from other studies, by remaining within the range of average values of 0.0015–0.0043 m s –1 ; (2) VR and DA significantly impacted [NH3 ] profiles and PTC ( p  < .001) and (3) changing slurry pit from 0.10 to 0.90 m HH did not significantly impact [NH3 ] or PTC ( p  = .756 and p  = .854, respectively). GRAPHICAL ABSTRACT: